Exercise physiology for health, fitness, and performance - Smith, Denise L.; Plowman, Sharon A.; Ormsbee, Michael J.
Dynamic, engaging, and up to date, Exercise physiology for health, fitness, and performance, sixth edition, prepares you for success in your courses and throughout your career. Updated throughout to reflect current research and emerging topics, this approachable text integrates basic exercise physiology with the latest research studies to demonstrate how fundamental principles can be applied to the widest possible variety of professional practice situations